Studies in Övdalian Morphology and Syntax: New research on a lesser-known Scandinavian language - Janne Bondi Johannessen (Linguistik Aktuell/Linguistics Today, 2015)
Övdalian is spoken in central Sweden by about 2000 speakers. Traditionally categorized as a dialect of Swedish, it has not received much international attention. However, Övdalian is typologically closer to Faroese or Icelandic than it is to Swedish, and since it has been spoken in relative isolation for about 1000 years, a number of interesting linguistic archaisms have been preserved and innovations have developed. This volume provides seven papers about Övdalian morphology and syntax. The papers, all based on extensive fieldwork, cover topics such as verb movement, subject doubling, wh-words and case in Övdalian. Constituting the first comprehensive linguistic description of Övdalian in English, this volume is of interest for linguists in the fields of Scandinavian and Germanic linguistics, and also historical linguists will be thrilled by some of the presented data. The data and the analyses presented here furthermore challenge our view of the morphosyntax of the Scandinavian languages in some cases - as could be expected when a new language enters the linguistic arena.